Perceptual-cognitive training effect on the development of anticipation skills in tennis serve return - Carboch, J.; Mrazova, K.; Brenton, J. (International Journal of Sports Science & Coaching, 2025)
Perceptual training can be used to develop anticipation skills, however, is not commonly integrated into tennis practice sessions. The aim of this study was to assess the effect of perceptual-cognitive training based on video recordings of tennis serves, modified by temporal occlusion, on the development of anticipatory skills of high-performance tennis players and tennis beginners. A total of 32 participants were divided into intervention and control groups based on skill level. We used pre and post-test design with intervention and control groups. The intervention group underwent a 3-week video-based perception training program. Results revealed a perception-cognitive training led to greater anticipation performance in the intervention group of high-performance players compared to beginners. Furthermore, improvements were observed in specific occlusion conditions across skill levels with key moments of racket-ball contact. These findings indicate that video-based perceptual training can effectively enhance visual anticipation development of tennis players, and ought to be included as a method in the comprehensive training of tennis players.